Efficacy of pyroligneous acid from Rhizophora apiculata on pathogenic Candida albicans - Darah Ibrahim, Jain Kassim, Lim Sheh-Hong and Wendy Rusli (Journal of Applied Pharmaceutical Science, 2013)
Rhizophora apiculata pyroligneous acid which is a crude condensate produced from the distillation of smoke generated in the process of charcoal making has the potential to be used as antifungal agent especially to treat candidal infections. In this study, pyroligneous acid (PA), concentrated pyroligneous acid (CPA), Dichloromethane extracts of CPA namely DCM A and B were tested against four pathogenic strains of Candida albicans. The results exhibited significant inhibition zones within the range of 7.00 -8.00 mm for PA, 16.00-17.00 mm for CPA, 16.00-18.00 mm for DCM A and 19.00-22.00 mm for DCM B. The results also revealed that extract DCM B of CPA was the most potential to be used as anticandidal agent with the minimum inhibitory concentration values between 3.13-6.25 mg/mL. Scanning electron micrographs of DCM B treated C. albicans cells confirmed the damaged cells caused by the extract.
Keywords: Rhizophora apiculata, Candida albicans